Effects of lactate administration on hypertrophy and mTOR signaling activation in mouse skeletal muscle. Issue 16 (22nd August 2022) - Shirai, Takanaga; Kitaoka, Yu; Uemichi, Kazuki; Tokinoya, Katsuyuki; Takeda, Kohei; Takemasa, Tohru
Abstract: Lactate is a metabolic product of glycolysis and has recently been shown to act as a signaling molecule that induces adaptations in oxidative metabolism. In this study, we investigated whether lactate administration enhanced muscle hypertrophy and protein synthesis responses during resistance exercise in animal models. We used male ICR mice (7–8 weeks old) were used for chronic (mechanical overload induced by synergist ablation: [OL]) and acute (high‐intensity muscle contraction by electrical stimulation: [ES]) resistance exercise models. The animals were intraperitoneally administrated a single dose of sodium lactate (1 g/kg of body weight) in the ES study, and once a day for 14 consecutive days in the OL study. Two weeks of mechanical overload increased plantaris muscle wet weight (main effect of OL: p  < 0.05) and fiber cross‐sectional area (main effect of OL: p  < 0.05), but those were not affected by lactate administration. Following the acute resistance exercise by ES, protein synthesis and phosphorylation of p70 S6 kinase and ribosomal protein S6, which are downstream molecules in the anabolic signaling cascade, were increased (main effect of ES: p  < 0.05), but lactate administration had no effect. This study demonstrated that exogenous lactate administration has little effect on the muscle hypertrophic response during resistance exercise using acute ES and chronic OL models. Our results do not support the hypothesis that elevated blood lactate concentration induces protein synthesis responses in skeletal muscle. Abstract : In this study, we examined the effects of lactate administration on the activation of exercise‐induced protein synthesis signals and muscle hypertrophy using acute and chronic resistance exercise models. We found no effect of lactate on the acute or chronic exercise models with respect to hypertrophy and exercise‐induced mTORC1 signaling."